Shared collections to shared storage: the CARM1 and CARM2 print repositories - Jilovsky, C.; Genoni, Paul (Emerald Group Publishing Limited, 2014)
Purpose – This paper aims to provide a case study of the CARM (CAVAL Archival and Research Materials Centre) Centre, a print repository owned and managed by CAVAL, an Australian consortium of academic libraries, based in Melbourne, Australia. The history, business models and operations of the initial module, CARM1, which commenced operations in 1996 and the recently completed module, CARM2 are described. This is preceded by a review of literature addressing the issue of retained or ceded ownership of stored items, and is followed by a discussion of the trend from a shared collection to shared storage within a shared facility. Design/methodology/approach – The approach is descriptive and explanatory. CARM1 was designed for both operations and space utilisation to be managed as economically as possible. This was achieved by storing items in a high density configuration and the collection, now known as the CARM Shared Collection, being owned by the CAVAL consortium. In exploring options for an expanded facility in 2007, a shared storage facility was determined to best meet the qualitative needs of member libraries. This option minimised the set-up and operational costs and required the lowest initial capital. CAVAL constructed a second storage facility, CARM2 which began operations in late 2010.Findings – The CARM Centre demonstrates that variant models for storage configurations and collection ownership can co-exist and meet the differing needs of member libraries within one facility. The need for off-site storage and the terms and conditions under which member libraries are willing to accept it differ widely. CAVAL's approach has been, and continues to be, that each member library makes its own decision and that CAVAL's role to facilitate those decisions while retaining an approach that supports broad-based solutions, be this in the form of a fully integrated shared collection, or a co-ordinated and carefully managed shared storage facility. Originality/value – This paper will be of interest and value to other organisations or consortia with an interest in the development, business models, implementation and management of shared print repositories that respond to the needs and circumstances of their member libraries.